Ability emotional intelligence profiles and real-life outcomes: a latent profile analysis of a large adult sample - Haag, Christophe; Bellinghausen, Lisa; Poirier, Clément (Frontiers in Psychology, 2025)
Few studies have examined emotional intelligence (EI) following a person-centered approach to identify different types of EI profiles and their relationship to everyday life outcomes. Even rarer are those using an “ability” approach of EI (AEI) and related “performance-based” tests, which are considered promising. This study fills this gap by identifying AEI profiles and linking them to everyday outcomes such as health, wellbeing, and decision-making. The QEg (“QE” for Emotional Quotient - Quotient Emotional in French - and “g” for the general population), an ability-based measure of EI, along with other measures, was administered to 2,877 French adults. We then ran latent profile analysis (LPA) and identified three latent profiles within a heterogeneous population. The full emotion processing (FEP) profile outperforms the two others on key domains of life such as stress perception, home-work interaction, gratitude and satisfaction with life, emotional burnout prevention, and decision-making. Our research reveals the need for individualized AEI training programs tailored to three distinct profiles, addressing foundational skills for those with minimal or partial emotional processing while refining existing strengths for those with full emotional processing. Targeting interventions to specific profile characteristics could enhance the effectiveness of AEI training and promote improved wellbeing and life outcomes.